(untitled) (Advancements in Homeopathic Research, 2022)
Objectives of Research The prime objectives of research are • To discover new facts • To verify and test important facts • To analyse an event or process or phenomenon to identify the cause and effect relationship • To develop new scientific tools, concepts and theories to solve and understand scientific and nonscientific problems • To find solutions to scientific, nonscientific and social problems and • To overcome or solve the problems occurring in our everyday life.